Brand Personality in Chile: a combinedemic-etic approach: a combined emic-etic approach - Olavarrieta, Sergio; Friedmann, Roberto; Manzur, Enrique (Estudios de Administración, 2010)
The purpose of our study is to extend previous work on brand personality (Aaker 1997). While following Aaker’s recommended methodology, we did so in the context of an emerging market economy such as Chile, and using a combined emic-etic research approach. Then, we investigated the cross-cultural applicability of the construct and we also look into the applicability of the measurement instrument developed by Aaker (1997). After several validation studies, six brand personality dimensions were found instead of the original North American based study, with tradition being the new Chilean dimension. This is consistent with previous work finding nation-specific dimensions in Japan, Spain, and France (i.e. Aaker, Benet-Martinez, Garolera, 2001; Koebel and Landwein, 1999). Insights for the understanding and management of brand images in international contexts, complementing parallel work done in other developed nations are derived.